Comparative Efficacy Of Dapagliflozin And Empagliflozin For Blood Pressure Control In Type 2 Diabetes Mellitus With Hypertension - Mariam, Ezza; Siddiqi, Fuad Ahmad; Qureshi, Muhammad Naeem; Hassan, Fayyaz; Yaseen, Laila; Siddiqi, Kanaz Ahmad (Journal of Rawalpindi Medical College, 2025)
Objective: To find out the efficacy of empagliflozin and dapagliflozin for blood pressure control in patients having type 2 diabetes mellitus with hypertension. Methods: A Quasi-experimental study was performed at the Medicine department of Tertiary Care Hospital, Rawalpindi, from March 2024 to September 2024. All patients were categorised into two groups, with group A receiving Empagliflozin (10 mg), while group B received Dapagliflozin (10 mg). Initial measurements were taken from both groups and repeated after three and six months of treatment to evaluate changes in HbA1c levels and blood pressure. SPSS-24.0 was used for all the above-mentioned analyses. Differences between groups at baseline and 3 months were analysed using independent samples t-tests. Within-group differences measured at baseline and 3 months were analysed using paired-sample t-tests, with p ≤ 0.05 considered statistically significant. Results: A total of 128 patients were included in this study, out of which 64 received 10 mg of dapagliflozin, while the other 64 received 10 mg of empagliflozin. HbA1c was decreased by 2.35% and 3% after 3 months and 6 months, respectively, by using 10mg dapagliflozin. In the empagliflozin group, this level was reduced by 2.70% and 3.40% after treatment of 3 and 6 months, respectively. Blood pressure was also decreased significantly in both groups, with a value of p<0.001. Conclusion: In conclusion, both empagliflozin and dapagliflozin have similar effects on significantly reducing the HbA1c level and blood pressure in patients with T2DM and hypertension. Keywords: Empagliflozin, Dapagliflozin, Hypertension, Type 2 Diabetes Mellitus